Digital Literacy Analysis of Elementary School Teachers on Distance Learning Instructional Process in Yogyakarta - Suwarjo Suwarjo; Haryanto Haryanto; Wury Wuryandani; Ainun Mahfuzah; Ratna Hidayah; Vera Yuli Erviana (AL-ISHLAH: Jurnal Pendidikan, 2022)
A teacher must have digital literacy to be able to understand of information or learning resources access such as online videos, eBook’s, recordings, audio, and digital libraries from the internet and use their features in designing learning media for learning resources used during online learning. This study aimed to analyze the digital literacy of elementary school teachers. Data were collected from 153 teachers from 44 schools in the special province of Yogyakarta. The research method uses a survey method that includes seven aspects of digital literacy: information literacy, Digital scholarship, Learning skills, ICT literacy, Career and identity management, Communication and collaboration, and media literacy. The results show that all teachers use technology in the online learning process including teachers aged 40 years. It also can be used as motivation and reference for teachers to improve digital literacy/and educational institutions carrying out of training to improve digital literacy for elementary school teachers.